PROJECT BASED LEARNING IN PROMOTING LEARNER AUTONOMY - Mimin Aminah; Ida Maulida; Tri Fitri Supriadi (LPSDI Bina Patria, 2023)
Students active learning in EFL Class is a necessity because language learning without practicing decrease the effectivity of learning achievement. In today curriculum no more teacher centered at class, the curriculum demand student active learning through teaching learning process. As a consequence, the teacher required to find the appropriate activity to make sure their students learning activity will always be continuing even beyond the class hour. This research tried to investigate the implementation of project-based learning on EFL Class and its effect on student learning autonomy. This study employs descriptive qualitative research design at University Students. The qualitative data collected through document analysis and observation. The result of data analysis shows that Project-based Learning improve students self-learning awareness, self-instruction, self-direction that reflect a learning autonomy activity. Due to the data result it can be concluded that Project-based Learning one of effective activity to be alternative to improve students learning autonomy.